Review on Hydrological Effects of Eucalyptus Plantation - HUANG Jun; JIN Pingwei; JIANG Xuebing (Renmin Zhujiang)
This paper reviewed the research progress of hydrological effects of eucalyptus plantations at home and abroad,and analyzed the research results of eucalyptus plantations such as evapotranspiration and vegetation interception,rainfall production and soil water.On the whole,there is no research conclusion that eucalyptus plantations are “pumping machines”,but the negative impact of eucalyptus plantations on regional water cycle and water balance does exist.Evaporation of eucalyptus plantations,rainfall interception,forest land flow and soil water are affected by factors such as species and age,canopy structure,rainfall and rotation system.The evapotranspiration rules of single eucalyptus and eucalyptus plantations were basically the same,and the daily evaporation was between 0.5 mm and 6.5 mm,which was significantly higher than that of other forest stands,and showed a trend of first increasing and then decreasing with the increase of tree age.The rainfall interception in different eucalyptus plantations varied greatly,generally accounting for 10%~30% of rainfall,and there was a positive correlation with rainfall overall,and the trend of increasing first and then decreasing with the increase of tree age.After the establishment of eucalyptus plantations,the surface runoff production in the area decreased significantly,especially in dry years.However,after felling,the base flow,runoff and peak flow of the catchment area gradually increased and returned to pre-afforestation levels.After the establishment of eucalyptus plantations,soil water content and water storage showed a downward trend,and the negative effect on soil water gradually decreased with the increase of tree age.However,short-cut eucalyptus plantations had a great negative impact on soil water,and it was difficult to effectively replenish soil water even in the rainy season with abundant rainfall.At present,there are still many problems in the research on the hydrological effects of eucalyptus plantations in China,and the follow-up should strengthen the long-series multi-temporal and spatial scale positioning monitoring,carry out the research and development of physical hydrological models of eucalyptus plantations,and provide technical support for the construction,felling management and soil water use regulation of eucalyptus plantations.